ISLAM WETU TELU DI BAYAN LOMBOK: DIALEKTIKA ISLAM NORMATIF DAN KULTURAL - Zuhdi, Muhammad Harfin (IAIN Pekalongan, 2009)
Islam reached Lombok island at sixteenth century, approximately at 1545. Its well known spreader was an expedition from Java led by Sunan Prapen son of Sunan Giri, one of the famous Wali Songo. Before Islam reached this island, according to some historian, the indigenous Sasak –appellation to indigenous of Lombok people—had their own traditional religion, Boda. Islam –since the very beginning of its history and will continuosly last to the end of time—has faced some different even contradictive values of local traditions and cultures. Its leads to a kind of dialectical process, and in turn produces what is called local Islam such as Islam Wetu Telu in Bayan, West Lombok. This article is aimed at revealing historical root of religious identity of Sasak community. Historical sketch of its religious identity leads to Wetu Telu religion that was collaboration of tradition, cultural and relegious values of the comers and those of the indigenous people in the past. Another point of view sad that Wetu Telu religion is an uncompleted process of islamization toward Waktu Lima religion that is considered by presently most Muslims in Lombok the true and pure Islam.